Private Participation in Infrastructure Projects in the Republic of Korea - Noumba Um, Paul; Dinghem, Severine (World Bank, Washington, DC, 2012)
In the aftermath of the 1997 East Asian financial crisis, the government of the Republic of Korea published a Private Participation in Infrastructure (PPI) Act to remove the main impediments to private investment in infrastructure sectors. The implementation of the Act was followed by a steady increase in the number of PPI projects, thus spurring the modernization of the main infrastructure facilities in transport, water, electricity, and telecommunications. Despite this progress, the Korean PPI market still faces critical challenges that are probably related to its nascent stage of development. The market is dominated by five construction and engineering firms, but lacks world-class project developers. At the same time, the procurement of PPI projects takes on average four years, and competition in tenders is limited. The number of unsolicited proposals is abnormally high, whereas the number of solicited proposals remains flat. The participation of foreign firms is very limited despite the size of the market and the number of projects awarded. Although local financing is available, the maturity of financing instruments does not exceed five years for most corporate papers, and 10 years for government bonds. This paper reviews the procurement of PPI projects in Korea and benchmarks it to international best practices before proposing options for its improvement.